Cover Image. Issue 7 (17th July 2019) - Yu, Shikai; Ji, Hongwei; Lu, Yuyan; Chen, Shanquan; Xiong, Jing; Chi, Chen; Teliewubai, Jiadela; Fan, Ximin; Blacher, Jacque; Li, Jue; Zhang, Yi; Xu, Yawei
Abstract : The cover image is based on the Original Paper Significance of the combination of inter‐limb blood pressure differences in the elderly: The Northern Shanghai Study by Shikai Yu MD et al., DOI10.1111/jch.13588 Supported by: Northern Shanghai Study